PERAN GURU AQIDAH AKHLAK DALAM MEMBENTUK PENDIDIKAN KARAKTER MELALUI KETELADANAN DAN PEMBIASAAN DI MADRASAH TSANAWIYAH MANSYAUL ULUM - Zainal Arifin; Zainuddin Fanani (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study examines the role of Aqidah Akhlak teachers in shaping student character at MTs Mansyaul Ulum. The research employed a qualitative approach, with data collected through interviews, observations, and documentation; the analysis was descriptive in nature. The results indicate that character education has been systematically integrated into the learning process, with teachers serving as role models, educators, and supervisors. Habit-forming strategies such as the 3S (Smile, Greeting, and Greeting), congregational prayer, and prayers before and after activities effectively instill religious values, discipline, and honesty, while fostering a sense of community and empathy. Although challenges such as tardiness and non-compliance with the school uniform still exist, particularly among ninth-grade students, significant progress is evident in punctuality, the orderliness of the learning process, and adherence to school regulations. This results in students who are not only academically intelligent but also possess integrity. Aqidah Akhlak teachers play a strategic role as catalysts for the transformation of Islamic values, supporting the formation of a generation with strong faith and contributing positively to society. The continuation of this program will strengthen the effectiveness of character education.